1974
DOI: 10.1111/j.1151-2916.1974.tb10901.x
|View full text |Cite
|
Sign up to set email alerts
|

Translucent Sintered MgAl2O4

Abstract: A translucent polycrystalline MgAI,O, ceramic was prepared from finely divided coprecipitated spinel in which a small amount of CaO added as a sintering aid was uniformly distributed. The CaO promotes densification through the formation of a liquid phase at the sintering temperatures. Depending on the sintering treatment, the relative density of the sintered spinel was 99.7 to -100% of theoretical. The in-line optical transmission was > 10% from 0.3 to 6.5 pm. Total transmission in the visible region was betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(46 citation statements)
references
References 1 publication
0
46
0
Order By: Relevance
“…13), 14) The transmission level attained after the AS stage, while demonstrating the high sinterability of the FSP powder, is not high enough for the intended application. In order to further reduce the residual porosity, under the 0.01 vol% required for good transmission, 6) the use of HIPing proved necessary.…”
Section: Jcs-japanmentioning
confidence: 99%
“…13), 14) The transmission level attained after the AS stage, while demonstrating the high sinterability of the FSP powder, is not high enough for the intended application. In order to further reduce the residual porosity, under the 0.01 vol% required for good transmission, 6) the use of HIPing proved necessary.…”
Section: Jcs-japanmentioning
confidence: 99%
“…After being shown to be transparent in early 1960's, spinel has received considerable attention and has been the subject of numerous studies. 1,2,6,8,[10][11][12] It has been considered to be well suited especially for armor applications because of its ideal combination of optical transparency, hardness, impact resistance, strength, modulus, ease of fabrication and crystal size capability. [3][4][5] In various studies, it has been shown to be superior to other available armor materials such as sapphire, AlON, soda-lime silicate glass and MgF 2 in terms of its excellent balance of performance and affordability.…”
Section: Introductionmentioning
confidence: 99%
“…There are extensive research efforts all over the world to improve the process for producing well-known transparent Lucalox and Yttralox (90 mol.% Y 2 O 3 -10 mol.% ThO 2 solid solution) materials and to obtain new types of transparent functional ceramics with complex physical composition and specific characteristics [3][4][5][6][7][8][9][10][11]. These include x-ray scintillators, ceramics resistant in vapors of alkaline and rare-earth elements, indium, and zinc, ceramics for instrumented optics (lenses, laser materials (Y 2 O 3 -ThO 2 -Nd 2 O 3 ), and materials with electrooptic effect (lanthanum-doped lead titanate-zirconate Pb, La(ZrTi)O 3 ).…”
Section: Introductionmentioning
confidence: 99%